Phytoremediation of bauxite wastewater potentiality by Jatropa curcas - Kristanti, Risky Ayu; Mardarveran, Priyatharishini; Almaary, Khalid Salmeen; Elshikh, Mohammad Soliman; AbdelGawwad, Mohamed Ragab; Tang, Kuok Ho Daniel (Springer Science and Business Media Deutschland GmbH, 2023)
Bauxite wastewater creates soil contamination and produces toxic effects on human health such as respiratory and skin rash problems. In this study, we investigated the phytoremediation ability of Jatropha curcas to remove bauxite wastewater from soil. Pot experiments were conducted to investigate the bauxite wastewater on the phytoremediation potential of J. curcas grown in contaminated soils. J. curcas exhibited a significant increase in plant growth leaf, root activity, plant height, and plant shoot when grown in bauxite contaminated soils compared with J. curcas grown in uncontaminated soils after 30 d treatment. Under bauxite exposure, a higher aluminium removal (88.5%) was observed in soils planted with J. curcas than unplanted soils (39.6%). The bioconcentration factor was also found to be 5.62, indicating that J. curcas have great tolerance and hyperaccumulator of aluminium under high aluminium concentrations and are capable of phytoextraction of soil contaminated with bauxite wastewater.